Agriwater: An R package for spatial modelling of energy balance and actual evapotranspiration using satellite images and agrometeorological data. (October 2019) - de Oliveira Ferreira Silva, César; Heriberto de Castro Teixeira, Antônio; Lilla Manzione, Rodrigo
Abstract: Aiming to subsidize the rational water resources management, an R package called "agriwater" was created in order to obtain the energy balance on the soil and actual evapotranspiration using satellite imagery and agrometeorological data. This package apply the Simple Algorithm for Evapotranspiration Retrieving - SAFER to calculate the evapotranspiration fraction E T r (or E T A E T 0 −1 ), actual evapotranspiration ( E T A ) and latent heat flux (λE); the Slob equation calculate the net radiation ( R N ); ground heat flux (G) is modeled from R N ; and the sensible heat flux (H) is retrieved as the residue of the energy balance equation. Landsat-8 (with and without thermal bands), Sentinel-2 and MODIS digital images can be used. Results are presented in raster format and can be post-processed by GIS analysis or anothers R procedures. A study case using Sentinel-2 images and agrometeorological data of a semiarid area from Brazil was performed. The requirements and conditions for use of the package are explained. Highlights: This package can use Sentinel-2, Landsat-8 or MODIS images, providing daily analysis at 10, 30- and 250-meters resolution. The Simple Algorithm for Evapotranspiration Retrieving was applied in tropical, semiarid, subtropical and wetland areas. Actual evapotranspiration, surface temperature, albedo, latent, sensible, and ground heat fluxes are spatially retrieved. No crop or soil classification, nor extreme thermohydrological conditions (to set hot and cold pixels) is needed. Results are in the form of raster file, which can be post-processed by using R or GIS-based software.